Dampak Harga Kopi terhadap Sosial Ekonomi dan Penerimaan Petani di Kelurahan Tangsi Baru Kecamatan Kabawetan Kabupaten Kepahiang - Sutina Sutina; Herri Fariadi; Rika Dwi Yulihartika (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Based on data from the Badan Pusat Statistik Kabupaten Kepahiang, the average household income in Tangsi Baru Village is projected to increase by 15% by 2025. Although rising coffee prices can benefit farmers, the socio-economic impacts must be considered. The cost of living may increase along with higher income, which can place additional financial pressure on households. This study aims to examine the impact of rising coffee prices on the socio-economic conditions of coffee-farming households and to analyze farmers’ income in Tangsi Baru Village, Kepahiang Regency. This research employs quantitative descriptive analysis and income analysis methods. The results show that increasing coffee prices have social impacts on farming households. The level of family education has improved (87.80%), land boundary conflicts have occurred (41.46%), social interaction has declined (51.22%), changes in social status have emerged (39.02%), and shifts in farmers’ lifestyles have taken place (65.85%).The economic impacts of rising coffee prices on farming households in Tangsi Baru Village include changes in livelihoods (82.93%) and changes in farming patterns (85.36%) and The average coffee farming income is IDR 7,258,000 per harvest per farmer.